Visual Audit Assistance for the Building Feasibility of Yayasan Pendidikan Anak Buta YPAB Surabaya: Pendampingan Audit Visual Kelayakan Bangunan Yayasan Pendidikan Anak Buta YPAB Surabaya - Hayati, Arina; Bararatin, Kirami; Muchlis, Nurfahmi; Krisdianto, Johanes; Cahyadini, Sarah; Defiana, Ima; Setyawan, Wahyu; Iranata, Data (Universitas Lancang Kuning, 2024)
According to UU No. 28 of 2002 concerning Buildings (UUBG), the reliability of school buildings needs to be ensured to accommodate the learning activity of students and teachers. This issue should be a great concern, especially for special schools. This community service program aims to help non-productive communities access reliable learning facilities through visual audit assistance. The community service program consists of four stages, namely the inventory of school buildings technical data, document inspection, visual audit, and reports of audit result. The results of this community service are a report of SMPLB-A YPAB buildings condition, a report of visual audit results, and dissemination of visual audit results. This community service supports SDG 11, Sustainable Cities and Communities, particularly in the improvement of environment quality and inclusive communities within the context of school building.